Pair production in a Color Glass Condensate background - Estivill, Patricia Gimeno (2023)
At high energy, the density of gluons in hadrons strongly increases until saturation, leading to a state of condensed gluon matter. In high energy collisions, the interaction of partons with this dense gluonic state is represented through Wilson Lines in the Color Glass Condensate theory, which describes the properties of small-x gluons in the saturated regime. In relativistic proton-nucleus collisions, the proton can be treated as a dilute system where a gluon fluctuates into a quark-antiquark pair. In this thesis, the interaction of these gluon and quark/antiquark partons with the condensed gluon matter in the nucleus is studied. Concretely, the quark pair production amplitude is calculated using the dilute-dense approximation in the covariant and in the Light Cone Perturbation theories. Firstly, in covariant theory the proton and nucleus are described as classical fields originating from color sources. As another approach, the initial gluon and the final quark-antiquark states are expanded in terms of the Fock state basis in Light Cone Perturbation Theory. A comparison of the two results is made at the end.